Territorial rural development strategies based on organic agriculture: the example of Valposchiavo, Switzerland - Stotten, Rike; Froning, Paul (Frontiers in Sustainable Food Systems, 2023)
The disembedding nature of globalization is being tackled by integrated and territorial approaches that focus on local contexts and include multiple actors and sectors. One example are biodistricts that rely on values of organic agriculture to strengthen territorial agro-food systems. The remote rural mountain valley of Valposchiavo, Switzerland, follows such a territorial approach and is subject of this case study. In this article we aim to understand in detail the processes of territorial development strategies in Valposchiavo. To shed light on the development approach, we used the theoretical concept of neo-endogenous development by Ray. We conducted document analysis, secondary interview analysis as well as problem-centered interviews. The results indicate that the rural development approach follows a neo-endogenous development that renews rural–urban linkages by developing internal and external networks. The creation of a territorial brand and a regional development project contribute to the establishment of local and organic agro-food supply chains. The territorial development approach in Valposchiavo demonstrates how remote mountain areas can shape the well-being of their community and tackle negative impacts of globalization.